L’idea di natura in Arne Næss - Valera, Luca (Filosofia, 2019)
The aim of the present paper is to analyze the idea of ‘nature’ in the context of the ‘Ecosophical thinking’ elaborated by Arne Næss, the ‘father’ of the Deep Ecology Movement. This analysis leads us to deepen the main characteristics of nature – i.e., richness, diversity, vitality, unity, etc. – and to identify the attribute of ‘perfection’ as a synthetic point of all these dimensions. It is also argued that the idea of ‘nature’ developed by Næss is substantially inspired by an interpretation of Baruch Spinoza’s Ethics. Finally, we highlight how this idea of nature is central in the work of the Norwegian philosopher, as it sustains the ethical, political and aesthetic implications outlined in the Deep Ecology Manifesto. In this regard, it is possible to understand Næss’s statement about the supremacy of environmental ontology and realism over environmental ethics.